2017
DOI: 10.1111/pcmr.12651
|View full text |Cite
|
Sign up to set email alerts
|

Lessons of a day hospital: Comprehensive assessment of patients with albinism in a European setting

Abstract: Albinism is a rare genetic disease, comprising syndromic and non-syndromic forms. We assessed clinical and genetic characteristics in a prospective evaluation of 64 patients (33 children and 31 adults) seen at a specialized day hospital. Causative genetic mutations were found in TYR (23/64, 35.9%), OCA2 (19/64, 29.7%), TYRP1 (1/64, 1.6%), SLC45A2 (12/64, 18.7%), C10orf11 (1/64, 1.6%), HPS1 (3/64, 4.7%), HPS5 (1/64, 1.5%), HPS6 (1/64, 1.6%) and GPR143 (2/64, 3.1%). Causative mutations remained undetermined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 34 publications
7
40
5
Order By: Relevance
“…In this study, comprehensive analysis of all currently known nsOCA genes (TYR, OCA2, TYRP1, SLC45A2, SLC24A5, and LRMDA) in 114 nsOCA patients recruited from 18 provinces in China shows the prevalence of OCA1, OCA2, OCA4, and OCA6 is 65.79%, 14.03%, 6.14%, and 0.88%, respectively, and the left nsOCA with uncertain causative defect of molecule (13.16%). In our cohort, OCA1 is the most common type of nsOCA and OCA2 ranks as the second most common type of nsOCA, which are in accordance with what reported in Japanese (Suzuki & Tomita, 2008), non-Hispanic Caucasians (Hutton & Spritz, 2008a), Danes (Gronskov et al, 2009), in the population of a European setting at the albino day hospital (Marti et al, 2018), and in the group of the patients mainly from France who were originated from different countries worldwide . In this study, we OCA2_c.849C>A were confirmed to be pathogenic in further function study, two patients with those variants would be OCA2.…”
Section: Cutaneous Phenotype Of Oca1 Oca2 and Oca4 Patientssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, comprehensive analysis of all currently known nsOCA genes (TYR, OCA2, TYRP1, SLC45A2, SLC24A5, and LRMDA) in 114 nsOCA patients recruited from 18 provinces in China shows the prevalence of OCA1, OCA2, OCA4, and OCA6 is 65.79%, 14.03%, 6.14%, and 0.88%, respectively, and the left nsOCA with uncertain causative defect of molecule (13.16%). In our cohort, OCA1 is the most common type of nsOCA and OCA2 ranks as the second most common type of nsOCA, which are in accordance with what reported in Japanese (Suzuki & Tomita, 2008), non-Hispanic Caucasians (Hutton & Spritz, 2008a), Danes (Gronskov et al, 2009), in the population of a European setting at the albino day hospital (Marti et al, 2018), and in the group of the patients mainly from France who were originated from different countries worldwide . In this study, we OCA2_c.849C>A were confirmed to be pathogenic in further function study, two patients with those variants would be OCA2.…”
Section: Cutaneous Phenotype Of Oca1 Oca2 and Oca4 Patientssupporting
confidence: 92%
“…Among ten novel indels, nine frameshift indels can be classified as pathogenic variants and a variant OCA2 _c.2373_2375delCGT (p.Val792del) can only be classified as a variant with uncertain significance (VUS). Eight variants are in or flank splicing site, including three reported previously to be related to OCA (Marti et al, ; Rimoldi et al, ), and five novel variants ( OCA2 _c.646+3A>G, OCA2 _c.2140‐2A>G, OCA2 _c.2245‐11T>G, OCA2 _c.808‐3C>G, and SLC45A2 _c.1032+1G>T), four ( OCA2 _c.646+3A>G, OCA2 _c.2140‐2A>G, OCA2 _c.808‐3C>G, and SLC45A2 _c.1032+1G>T) of which in vitro splicing assay compared with WT in HeLa and ARPE‐19 cell lines, demonstrated that brought about change in splicing (Figure ) and no change was observed between WT and MUT for analysis of variant OCA2 _c.2245‐11T>G (Data not shown). Therefore, seven splicing can be classified as pathogenic variants and OCA2 _c.2245‐11T>G can only be classified as a VUS at the current stage.…”
Section: Resultsmentioning
confidence: 96%
“…Consanguinity was frequent in our group, with 26% of patients in consanguineous families, which is similar to that in Africa [23][24][25] and higher than in European countries, that is, 5-6% [26]. Contrary to our results, another study performed in Bahia, Brazil, reported inbreeding rates similar to those in Europe, with a prevalence of 7.5% [19].…”
Section: Discussionsupporting
confidence: 69%
“…A Tanzanian histological review of 134 biopsies from 86 patients with albinism diagnosed with skin cancer reported that the youngest patient was 18 years of age and the overall mean age for cancer 35 years [17]. The prevalence in our population (26%) was similar to that among patients with albinism in Tanzania (25%) [28], South Africa (23%) [32], and much higher than in Europe, that is, 4.6% in France and 0.5% in Italy [26,30].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation